CT Findings From Interstitial Lung Diseases in Patients With Metastatic Breast Cancer Treated With Fam-Trastuzumab Deruxtecan: A Single Institutional Experience - Jang, Yoon Jung; Jeong, Jae Ho; Kim, Jeong Eun; Ahn, Jin-Hee; Jung, Kyung Hae; Kim, Sung-Bae (Journal of breast cancer, 2022)
This single-institute, retrospective cohort study enrolled patients with human epidermal growth factor receptor 2-positive metastatic breast cancer treated with trastuzumab deruxtecan between August 2017 and January 2021 from four previous studies. Of 31 patients, 4 (12.9%) had interstitial lung disease (ILD). The dominant pattern observed on computed tomography was organizing pneumonia (100%), comprising subpleural consolidations in the lung periphery. However, no dominant distribution was observed in radiological lesions of the lungs. Of all the tested patients, lower lobe predominance was noted in 2 (50.0%) patients, upper lobe predominance in 1 (25.0%) patient, and diffused lobe distribution in 1 (25.0%) patient. All events were confined to the Common Terminology Criteria for Adverse Events grade 1 or 2 (100%). None of the patients died. Despite the small number of cases investigated, the incidence of trastuzumab deruxtecan-induced ILD in the Korean population was comparable to that previously reported.